(untitled) (BIRDEM Medical Journal, 2014)
Adult mature teratoma of testis is a rare tumour. A 53 year old gentleman was admitted in the department of Urology, BIRDEM with left hemi-scrotal swelling. Ultrasonogram of scrotum and CT scan confirmed it a solid tumour. Orchidectomy was done. Histopathology examination revealed adult mature teratoma. Birdem Med J 2014; 4(2): 115-118